Strengthening Entrepreneurial Skills and Motivation among University Students - Anis Marjukah; Dwi Wanito Ambarsari; Arif Julianto Sri Nugroho; Agung Nugroho Jati; Oki Kuntrayanto (Involvement International Journal of Business, 2025)
Entrepreneurship is increasingly promoted as a strategic response to graduate unemployment and economic inequality, particularly in developing countries. Higher education institutions are expected to foster entrepreneurial readiness among students by shaping their perceptions, stimulating interest, and building competence. This study employed a qualitative descriptive approach involving 20 purposively selected students from the Faculty of Economics and Psychology at Widya Dharma University who participated in the university’s entrepreneurship development program during 2023–2024. Data were collected through semi-structured interviews and supported by document analysis and field observations. Triangulation was applied to validate the findings. The results show that 75% of students agreed that entrepreneurship can improve welfare, while 70% viewed it as a viable alternative to formal employment. A total of 60% expressed interest in trying entrepreneurship due to adequate knowledge, and 55% were willing to start a business with institutional support. In terms of competence, 75% enjoyed creativity and innovation, and the same percentage were ready to face the risk of failure. However, only 50% believed they had the potential to be entrepreneurs. Although 60% felt unashamed to learn from others and saw student organizational involvement as beneficial, 60% also acknowledged the need for external support to achieve entrepreneurial success. These findings indicate that students’ entrepreneurial readiness is promising but still requires enhancement through practical experience and mentorship. The study proposes an integrated development model to cultivate entrepreneurial readiness by targeting three dimensions namely perception, interest, and competence.